HIGHER EDUCATION AND TEACHING MODERN PHYSICS IN IT - Saidov Safo Olimovich; Badriddinov Islombek Mustakham ugli; Kamolov Jurabek Jalol ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, some topical issues of teaching modern physics are analyzed about exactly what new courses should be introduced as a special subject for bachelors, masters, and teachers of retraining and advanced training courses for teachers of “Physics”, theoretical analysis and solutions of issues such as the scope of teaching selected disciplines, what criteria are used in their selection, its name, in particular, the term "modern physics", its content and differences from "classical" physics.